WOMEN IN THE OLD TESTAMENT AND THE QUR'AN - Mohd Zahid Itoo (UIN Walisongo Semarang, 2023)
The women’s rights movement is not unique to this period; it is a set of events that have occurred throughout history in various parts of the world. In contemporary times the status of women has been the subject of consideration and discourse. Generally, it is thought that religion has created a hindrance in the upliftment of women. However, the interpretation of sacred religious books and doctrines has played an important in framing women’s status. In this context, both the Old Testament and the Qur’an were comparatively studied to figure out women’s status. This study seeks to analyze the basic position of women in both religious scriptures. It also tries to uncover the place of refuge for women in the modern era where women are exploited. This study is descriptive and comparative in nature.